Role of the Pharmacist in Managing Treatment-Resistant Depression: A Focus on Ketamine - Linda Xing Yu Liu; Marina Golts; Virginia Fernandes (MDPI AG, 2021)
The impact of depression is well described in the literature, and it is most prominent in patients who have trialed multiple treatments. Treatment-resistant depression (TRD) is particularly debilitating, and it is associated with significant morbidity and mortality. Despite this, there seems to be therapeutic inertia in adopting novel therapies in current practice. Ketamine is an N-methyl-D-aspartate receptor antagonist and anesthetic agent which has recently been shown to be effective in the management of TRD when administered intravenously or intranasally. The treatments, however, are not easily accessible due to restrictions in prescribing and dispensing, high costs, and the slow uptake of evidence-based practice involving ketamine within the Canadian healthcare system. Given the limited treatment options for TRD, novel approaches should be considered and adopted into practice, and facilitated by a multi-disciplinary approach. Pharmacists play a critical role in ensuring access to quality care. This includes dissemination of evidence supporting pharmacological treatments and facilitating translation into current practice. Pharmacists are uniquely positioned to collaborate with prescribers and assess novel treatment options, such as ketamine, address modifiable barriers to treatment, and triage access to medications during transitions of care. Extending the reach of these novel psychiatric treatments in both tertiary and primary care settings creates an emerging role for pharmacists in the collaborative effort to better manage treatment-resistant depression.